The Choice of Prices vs. Quantities under Uncertainty - Markus Reisinger; Ludwig Ressner (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2007)
This paper analyzes a duopoly model with stochastic demand in which firms first choose their strategy variable and compete afterwards. Contrary to the existing literature, we show that firms do not always choose a quantity which is the variable that induces a smaller degree of competition. The reason is that demand uncertainty and the degree of substitutability have countervailing effects on variable choice. Higher uncertainty favors prices, while closer substitutability favors quantities. Moreover, for intermediate values firms choose different strategy variables in equilibrium.
urn:nbn:de:bvb:19-epub-13350-3
Keywords: D43; L13; 330; competition; strategy variables; demand uncertainty